Green Entrepreneurial Orientation and Performance of New Ventures - Ling, Jianyu; Abd Kadir, Hazlina Binti; Ahmad, Muhammad (International Journal of Global Economics and Management, 2026)
Currently, China's economy is undergoing rapid development, and new ventures are also experiencing swift growth. Consequently, the contradiction between development and the environment is intensifying. Therefore, the growth of the green economy is emerging as one of the crucial factors for the development of new ventures. Particularly in East China, under the guidance of green entrepreneurship, new ventures can enhance their operational efficiency by analyzing the driving factors of green entrepreneurship orientation, investigating the influencing factors of new ventures within the existing green entrepreneurship orientation, and analyzing the development of green entrepreneurship orientation in existing new ventures. Moreover, this study aims to analyze the mediating role of green and entrepreneurial orientation between its driving factors and corporate goals. This study will adopt the deductive research method to explore and evaluate the relationship among the driving factors of green entrepreneurship, green entrepreneurial orientation, and enterprise performance. The research will be grounded in the absorptive capacity theory, the Triple - Bottom - Line (TBL) theory, the stakeholder theory, and the natural resource - based theory. By leveraging the absorptive capacity to construct a theoretical framework, this paper explores the driving factors of green entrepreneurial orientation and the relationship between green entrepreneurial orientation and enterprise performance. Employing the paradigm of green economics, through the research framework of three analogous dimensions of society, environment, and economy, this paper focuses on enterprise performance and examines the relationship between the green entrepreneurial orientation of new ventures, its driving factors, and enterprise performance. This approach integrates the core concept of the enterprise green strategy and the green absorptive capacity theory of enterprises.